Fishing Technology in the Coastal Community of Kampung Mandar, Banyuwangi: A socio-economic studies - Dewi, Talitha Suksesiana; Putra, Febriano Guntur Dewangga; Sabrina, Anneta Rizkia; Adilah, Husnun (Diponegoro University, 2023)
Fishing gear is essential for fishing activities, and as a maritime nation, Indonesia boasts a rich diversity of marine resources. Many Indonesians rely on fishing for their livelihood. This study was conducted in Kampung Mandar, Banyuwangi Regency, and examines four key areas: the condition of the fishing community, the technology used by Mandar fishermen, fishing areas, and profit-sharing among fishermen. The research employed various methods, including literature review, interviews, and observation. The findings reveal significant differences in fishing gear among Kampung Mandar fishermen, with specific gear and areas designated for different types of fish. The majority of the Mandar fishing community consists of service fishermen, many of whom now use diesel engines for their boats. Variations in fishing gear, such as boat type, fishing lines, and the use of lights, highlight different fishing practices. The cooperative established by KUB Pondok Layar aims to mitigate issues that negatively impact fishermen. During the east season (June-October), many Mandar fishermen seek employment in urban areas, returning to the village for the west monsoon fishing season (November-May).